EKSISTENSI DAN EFEKTIVITAS LEMBAGA OMBUDSMAN DAERAH (LOD) DALAM RANGKA TERCAPAINYA GOOD GOVERNANCE DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Septi Nur Wijayanti (Jurnal Media Hukum, 2008)
The motivation to increase the bureaucracy of the government in the local government is not only carried out internally, but several efforts addressing the external aspect is also conducted as a part of the society’s concern in promoting a bureaucracy which is humanistic, efficient, accountable and respecting the human right. This concern is reflected in the institutionalization of the DIY ombudsman, which is also a part of the society’s effort to promote changes. The establishment of this institution is very strategic, particularly when it is dealing with the condition that the civil society is often unaware of their rights as the costumers of the public service. Besides, the local government has not been able to address the rights appropriately. Hence, the institution could function as a media for the civil society to file their complaints and aspiration to the executives. In addition, the institution could also work independently to protect the right of the civil people from the mal- administrative service conducted by the government officials. Based on the study on data of LOD of DIY, it is identified that LOD is trusted by the society in its efforts to build the good governance, although, on the other hand, not many people ever heard about this institution. In contrast, the government officials consider that the existence of LOD of DIY threaten their future career.